PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN EFISIENSI OPERASIONAL DAN KUALITAS PENGAMBILAN KEPUTUSAN ORGANISASI - Adrian Posman Imanuel; Rangga Primadillah; Yan Indah Surya Laowo; Nadira Matondang; Zahra Choirunnisa; Ines Heidiana Ikasa (Journal of Research and Publication Innovation, 2025)
The Management Information System (MIS) plays a crucial role in optimizing organizational performance through integrated data management and timely decision-making. This paper analyzes the contribution of MIS to operational efficiency and decision quality using literature-based research across recent academic studies. Results indicate that MIS enhances data accuracy, streamlines workflow, and provides strategic insights supporting managerial decisions. Effective MIS implementation requires strong leadership commitment, adequate technological infrastructure, and user competence. These findings reaffirm the significance of MIS as a strategic asset for achieving competitive advantage and organizational sustainability.